KENDALA PETUGAS REKAM MEDIS DALAM PENENTUAN KODE PENYAKIT TERHADAP KLAIM BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) DI RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Tri Purnama Sari (LPPM Universitas Abdurrab, 2016)
Medical record plays an important role in BPJS program particularly in BPJS patient registration as well as coding and claim. Determination of diagnosis codes patient are obligations, rights and responsibilities of docter (medical personnel) in accordance with the directives contained in the book ICD-10. But in fact, there are still obstacles from officers in determining disease codes for medical record file is incomplete. The purpose of this study was to determine the constraints attendant medical records in determining the disease code to claim BPJS in RSIA Eria Bunda Pekanbaru. The research method used descriptive research with a combination of quantitative and qualitative approaches. Informants are 4 people that officers conducting coding. Techniq and methods of data collection using interviews, observation and review of medical record file. These results indicate that the constraints medical records officers in determining of disease because the docter's diagnosis code is not complete. The high number of incompleteness diagnosis is the final diagnosis (secondary) as many as 46 items. The Human Resources to code patient disease of BPJS is sufficient. Standard Operating Procedure determination of disease codes has been no exists. Facilities and infrastructure already exists and is adequate. The suggestions of this research is a docter should immediately filling doctor's diagnosis on the medical resume of patient in order to medical officer was not constrained in determining the disease code because it contains data/information that can be used as a basis for determining rates BPJS claims. Medical records should continue to conduct training on coding and BPJS so that the officers more mastering in coding activities. Than, Standard operating procedures should be made to any standard set.